Decreased macular choriocapillaris in thyroid-associated ophthalmopathy: focusing on chorioretinal folds with and without optic disc edema - Zeng, Peng; Liang, Jia-qi; Peng, Yuan-yu; Fan, Shu-xian; Wang, Jing; Zhou, Shi-you; Tian, Peng; Wang, Mei (Frontiers in Endocrinology, 2023)
Purpose: To evaluate the vessel density (VD) of the macular choriocapillaris (CC) and retina in thyroid-associated ophthalmopathy (TAO) patients with chorioretinal folds (CRFs) with and without optic disc edema (ODE) and the correlations of these characteristics with visual function. Method: This was a cross-sectional study. Twenty TAO patients with CRFs (35 eyes) and 20 normal subjects (normal group, 40 eyes) were recruited at the Ophthalmology Department of the Sun Yat-sen Memorial Hospital from March 2018 to October 2022. Then, CRFs patients were divided into two groups, the ODE and non-ODE groups (NODE), based on the presence or absence of ODE. All the patients underwent optical coherence tomography angiography (OCTA) and the VD of the macular CC and retina was computed. The correlation of VD and visual function was analyzed. Results: Compared with normal group, the macular whole-image VD in retinal superficial layer (SLR-mwiVD: 49.82±3.38 in the normal group, 42.44±5.40 in the NODE group and 42.51±5.37 in the ODE group), deep layer (DLR-mwiVD: 51.05±6.23 in the normal group, 45.71±6.66 in the NODE group and 46.31±5.48 in the ODE group) and choriocapillaris (CC-mwiVD: 70.23±2.47 in the normal group, 68.04±3.73 in the NODE group and 63.09±6.51 in the ODE group) was decreased in NODE (all p＜0.05) and ODE group (all p＜0.01). There was no difference in these parameters except CC-mwiVD between the ODE and NODE groups. The CC-mwiVD in the ODE group (63.09±6.51) was significantly reduced compared with that in the NODE group (68.04±3.73, p=0.004). All these VD parameters were negatively correlated with BCVA, VF-PSD and P100 latency and positively associated with VF-MD, P100 amplitude and HRR scores (all p＜0.05). Conclusions: There was a significant decrease in the VD of the macular CC and retina of patients with CRFs with or without ODE, which was correlated with visual dysfunction. The VD of the macular CC in CRFs patients with ODE was significantly reduced compared with that in the NODE group, but similar results were not observed in the retina.